Contrastive Analysis of Adjective Asai in Japanese and Dangkal in Indonesian - N Ghaisani; D. Sutedi; N Haristian (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2023)
In Japanese, many words have more than one meaning. An example of a word in Japanese that has more than one meaning is adjective asai. Adjective asai in Indonesian doesn’t only mean dangkal (shallow) but has other meanings. Adjective asai that have more than one meaning can be contrasted with adjective dangkal in Indonesian. Using contrastive analysis method, this study aims to analyze the similarities and differences between adjective asai in Japanese and adjective dangkal in Indonesian based on their meanings. Data in this study were obtained from corpus and articles in online news in Japanese and Indonesian. The results of this study there were found the similarities of meanings in adjective asai and dangkal were found in the meaning 1) not deep or close to the surface. 2) knowledge, experiences and thoughts are not enough, and 3) the level of severity was low. While the differences between adjective asai and dangkal were found in the meaning 1) short time, 2) a tenuous or unclose relationship, 3) light color, 4) a faint or light smell, 5) light taste, and 6) petty. The results of this study are expected to be a reference in teaching adjective asai and dangkal as a foreign language, and being a solution for learners to reduce errors in the use of adjective asai and dangkal and errors in the translation of these two adjectives.